1995
DOI: 10.1029/94ja02743
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the linear theory of single‐species tearing in two‐dimensional quasi‐neutral sheets

Abstract: We have developed the linear theory of collisionless ion tearing in a two‐dimensional magnetotail equilibrium for a single resonant species. We have solved the normal mode problem for tearing instability by an algorithm that employs particle‐in‐cell simulation to calculate the orbit integrals in the Maxwell‐Vlasov eigenmode equation. The results of our single‐species tearing analysis can be applied to ion tearing where electron effects are not included. We have calculated the tearing growth rate as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…In an analytic study, Brittnacher et al (1995) showed that when ρ i /w 0 ≈ 1, the fastest growing linear mode occurs at kw 0 ≈ 0.5, where k is the wavenumber of the tearing mode, w 0 is the halfwidth of the current sheet, and ρ i is the ion gyroradius. Since…”
Section: Introductionmentioning
confidence: 99%
“…In an analytic study, Brittnacher et al (1995) showed that when ρ i /w 0 ≈ 1, the fastest growing linear mode occurs at kw 0 ≈ 0.5, where k is the wavenumber of the tearing mode, w 0 is the halfwidth of the current sheet, and ρ i is the ion gyroradius. Since…”
Section: Introductionmentioning
confidence: 99%
“…] in the normalized unit, with L x = 12D (the wavelength of the fastest growing mode [Brittnacher et al, 1995]), L y = 0.5, and L z = 8D. The choice of L y = 0.5 excludes any longerwave drift modes, such as the drift-kink instability (DKI) and the drift-sausage instability (DSI) [e.g., Ozaki et al, 1996;Lapenta and Brackbill, 1997;Horiuchi and Sato, 1999], from the present study.…”
mentioning
confidence: 99%
“…(4.14) from the approximate theory, and is compared in Fig. F21 with the analytical theory by Brittnacher et al (1995) and the full orbit approach. The current sheet for this comparison is an isotropic pair-plasma Harris type with ρ i /L = 1, T ⊥i /T ⊥e = 1, n b /n 0 = 0.…”
Section: Electron-positron Harris Sheetmentioning
confidence: 99%